Biocompatibility of Accelerated Mineral Trioxide Aggregate on Stem Cells Derived from Human Dental Pulp. - KARGÜL, BETÜL (ELSEVIER SCIENCE INC, 2016)
The aim of this study was to evaluate the effects of several additives on the setting time and cytotoxicity of accelerated-set mineral trioxide aggregate (MTA) on stem cells of human dental pulp. ProRoot white MTA (WMTA) (Dentsply Tulsa Dental, Johnson City, TN) was mixed with various additives including distilled water, 2.5% disodium hydrogen phosphate (Na2HPO4) (Merck, Darmstadt, Germany), K-Y Jelly (Johnson & Johnson, Markham, ON, Canada), and 5% and 10% calcium chloride (CaCl2) (Merck). The setting times were evaluated using a Vicat apparatus (Alsa Lab, Istanbul, Turkey). Human dental pulp stem cells were isolated and seeded into 48-well plates at 2 x 10(3) cells per well and incubated with MTA samples for 24 hours, 3 days, and 7 days. Cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium assay. MTA mixed with 10% CaCl2 showed the lowest setting time (P < .05). According to the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sullophenyl)-2H-tetrazolium results on the 1st, 3rd, and 7th days, a statistically significant difference was found (P < .05) between MTA groups and the control group. MTA mixed with K-Y Jelly in all groups showed the lowest cell viability at all time points (P < .05). The cell viability of MTA mixed with distilled water, 5% CaCl2, 10% CaCl2, and Na2HPO4 increased significantly through time (P < .05). This in vitro study found MTA mixed with 5% and 10% CaCl2 and Na2HPO4 is biocompatible with dental pulp stem cells in terms of cell viability. Further in vitro and in vivo investigations are required to prove the clinical applications of MTA mixed with various additives.
Keywords: Accelerators; biocompatibility; dental pulp stem cell; mineral trioxide aggregate; setting time; CLINICAL-APPLICATIONS; PORTLAND-CEMENT; MTA